Fe3O4@RB@LDH: Efficient and Recyclable Photocatalyst Visible‐Light Mediated Synthesis of Pyran and Pyrrolidinone Derivatives and Their Anti‐Microbial Activities. Issue 6 (8th February 2022) - Dutta, Arup; Goswami, Munmee; Rabha, Jintu; Das, Sukanya; Jha, Dhruva K.; Nongkhlaw, Rishanlang
Abstract: Selective and high yielding synthesis of pyran and pyrrolidinone derivatives through a magnetic layered double hydroxide (LDH) visible light photocatalyst (VLPC)‐promoted reaction is reported. The catalyst was prepared and characterized by various analytical techniques. Since it is magnetic the prepared catalyst could be easily separated from the reaction mixture by using an external magnet. The advantages of this synthetic protocol are good to excellent yields, short reaction times, easy catalyst recovery and recyclability. Also, in vitro antibacterial screening of pyrrolidinone derivative was studied against gram‐positive Bacillus cereus ( B. cereus ), gram‐negative bacteria Escherichia coli ( E. coli ) and S. aureus . Compound 9 f [Methyl‐2‐(3‐chlorophenyl)‐2, 5‐dihydro‐4‐hydroxy‐5‐oxo‐1‐phenyl‐1 H ‐pyrrole‐3‐carboxylate] exhibited the maximum activity against all the bacteria tested in the experiment. Abstract : Synopsis: This synthetic protocol establishes the synthesis of pyran and pyrrolidinone derivatives under visible‐light irradiation using a magnetic layered double hydroxide (LDH) as photocatalyst and anti‐microbial activities of the compounds. Shorter reaction times, good to excellent yields, operational simplicity, easy catalyst recovery as well as recyclability are worth mentioning. Among all the synthesized compounds, methyl 2‐(3‐chlorophenyl)‐2, 5‐dihydro‐4‐hydroxy‐5‐oxo‐1‐phenyl‐1 H ‐pyrrole‐3‐carboxylate displayed the maximum activity against all the bacteria tested in the experiment.